INOVASI ONIGIRI SEHAT DARI IKAN KEMBUNG SEBAGAI UPAYA PENCEGAHAN STUNTING: STUDI KASUS DI DESA KALIRANDUGEDE - Sujono, Rusny Istiqomah; Janah, Miftakhul; Ramadhan, Rizki; Nurpratiwi, Ela Dwi; Ngizzah, Nailul; Hermawan, Aris; Nurfaedah, Nurfaedah; Mutaqin, Fatih; Nurjanah, Siti; Fadhila, Nurma; Tirsardewi, Sartika; Ratnasari, Dwi; Emilda, Yufa (Jurnal Abdi Insani, 2024)
Stunting is a chronic nutritional problem that affects toddlers' growth, particularly when their height does not align with age standards. In Indonesia, the prevalence of stunting in 2022 was 21.6%, still above the WHO standard of 20%. In response, Alma Ata University, through the Real Work Lecture (KKN) Program, implemented a community-based intervention in Kalirandugede Village, Kendal, to reduce stunting rates. This program combines nutrition education and utilization of local potential with a participatory approach. One of the main activities is counseling on the importance of consuming animal protein, especially mackerel, which is rich in nutrition and affordable. Additionally, this program presents "Onigizi," an innovative mackerel-based onigiri that serves as a healthy alternative for families. This activity involves PKK mothers who are agents of change in their communities. Through demonstrations and direct practice, participants gain knowledge about the importance of balanced nutrition as well as skills in utilizing local food ingredients to prevent stunting. The program evaluation showed active participation and enthusiasm from participants in understanding stunting prevention and applying the knowledge gained. In conclusion, this program has not only succeeded in raising public awareness of the importance of nutrition but also offers practical solutions based on local potential. Other regions can replicate this approach as an innovative and sustainable model for eradicating stunting.